The Effect of upper Extremity Proprioception on Technical Performance in Handball players - Terzi, Esranur; Kayhan, RecepFatih; Çakır, Halil İbrahim (International Journal of Sports Medicine, 2025)
The aim of this study was to investigate the effect of upper extremity proprioception on free throw accuracy, speed and reaction speed in handball players. Fifteen professional male handball players were selected through random sampling. Proprioception was assessed with a goniometer, reaction speed with a light trainer system, and free throw speed with a sport radar. Linear regression analysis was used to determine the effect levels between variables. Our study determined that free throw speed, free throw accuracy, and reaction speed performances improved as proprioceptive sensory acuity increased during shoulder flexion (R2=between 0.280 and 0.659; p<0.05) and extension (R2=between 0.270 and 0.590; p<0.05), shoulder external rotation (R2=between 0.461 and 0.873; p<0.01), elbow flexion (R2=between 0.477 and 0.840; p<0.01) and extension (R2=between 0.275 and 0.574; p<0.05). In addition, it was determined that shoulder internal rotation proprioceptive sensory acuity had a positive effect on free throw accuracy and reaction speed performances (R2=between 0.338 and 0.415; p<0.05) except for free throw speed (p>0.05). We conclude that higher proprioceptive acuity enhances motor control of joints, contributing to enhanced athletic performance. Considering the decisive role of technical skills in score production, it is predicted that improving proprioceptive sense may improve the score performance of athletes by improving technical skills.
Keywords: free throw accuracy; free throw speed; handball; joint position sense; motor control; reaction speed